Analisis Kebijakan Restrukturisasi Pembiayaan Akibat Force Majeure Pada BMT Assyafi’iyah Berkah Nasional KC Metro - Almanda Dafitri; Haris Santoso; Eka Nurzanah (DPPM Universitas Pelita Bangsa, 2026)
This study analyzes the financing restructuring policy at BMT Assyafi’iyah Berkah Nasional KC Metro in response to force majeure events, such as natural disasters and significant business downturns. These conditions can reduce members’ ability to meet their obligations and increase the risk of Non-Performing Financing (NPF). The study aims to assess how the restructuring policy is implemented and how effective it is in assisting affected members. A descriptive qualitative method was used, with data collected through interviews, observation, and documentation. The results show that restructuring is carried out selectively through internal evaluation and board approval, effectively easing members’ burdens, maintaining business continuity, and controlling NPF. Therefore, the institution is advised to strengthen its monitoring and evaluation systems, as well as restructuring guidelines, and to enhance business support for its members. On the other hand, members are expected to understand the applicable procedures, maintain active communication when facing difficulties, and improve financial management so that obligations are met and the partnership can be sustained.